The twins: oxford literacy web - Graham, Elspeth; Newsham, Ian (Oxford University Press Oxford, 1999)
Fitting the requirements of the National Literacy Strategy, National Curriculum in England and Wales, English Language 5-14 in Scotland, and Common Curriculum in Northern Ireland, this book guides pupils through the core skills associated with learning to read and write with a diverse range of literary styles.